Disrupting marketing realities: A research agenda for investigating the psychological mechanisms of next‐generation experiences with reality‐enhancing technologies. Issue 8 (25th May 2022) - Hilken, Tim; Keeling, Debbie I.; Chylinski, Mathew; de Ruyter, Ko; Golf Papez, Maja; Heller, Jonas; Mahr, Dominik; Alimamy, Saifeddin
Abstract: Reality‐enhancing technologies such as augmented reality and virtual reality are rapidly becoming a part of everyday life. Seizing this moment, we set out a research agenda for studying the psychological mechanisms underpinning consumer experiences with these new technologies, structured around four application areas: (1) delivering innovative offerings, (2) supporting sustainability and consumer well‐being interventions, (3) balancing value cocreation and privacy concerns, and (4) achieving new modes and means of impact. For each area, we identify research directions that can guide the development and use of reality‐enhancing technologies for the realization of next‐generation consumer experiences. We explicitly balance potential advantages and disadvantages, thus encouraging researchers and practitioners to prioritize developing the "purpose" of these technologies, by focusing on the psychological mechanisms that underlie their use, over the technological development of their "pixels." In this way, we guide the impactful development of reality‐enhancing technologies for applications with significance for consumers and firms.